2019
DOI: 10.4102/sajr.v23i1.1749
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study correlating sonographic features of thyroid nodules with fine-needle aspiration cytology in a South African setting

Abstract: BackgroundThyroid nodules are prevalent worldwide. Detection rates are increasing because of the use of ultrasonography. Ultrasound has become the first-choice imaging modality in evaluating nodules. The decision to perform an US-guided fine-needle aspiration (FNA) is based on a nodule’s sonographic features. Thus, it is essential to accurately risk stratify thyroid nodules so that they are appropriately referred for FNA.ObjectivesThe aim of this study was to correlate the ultrasound imaging features of thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This may be due to the small cancer sample in our study. Hypoechogenicity was frequently found in malignant nodules, in agreement with the literature [2,33,34]. However, we did not find the irregular contour parameter as a predictive factor for thyroid cancer [33].…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to the small cancer sample in our study. Hypoechogenicity was frequently found in malignant nodules, in agreement with the literature [2,33,34]. However, we did not find the irregular contour parameter as a predictive factor for thyroid cancer [33].…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have indicated that no single ultrasound feature can directly and accurately predict the malignancy of a nodule ( 36 , 37 ); however, some characteristics, such as hypoechogenicity, irregular margins, taller-than-wide shape, microcalcifications and solidity, may predict thyroid cancer ( 14 , 16 , 17 , 19 , 20 , 38 ). In this study, solidity, hypoechogenicity, irregular margins, taller-than-wide shape, microcalcifications and posterior echo attenuation associated with malignant nodules, whereas regular halo associated with benign nodules.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant impact is noted in centres with a high rate of non-diagnostic reports. [8][9][10][11] The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) has resolved adequacy threshold issues for pathologists. [6,12] It was implemented at the TBH cytology laboratory and has been used since 2016.…”
Section: Researchmentioning
confidence: 99%